Trends and Factors Associated with Suicide Deaths in Older Adults in Ontario, Canada. - Novilla-Surette, Eada M. P.; Shariff, Salimah Z.; Le, Britney; Booth, Richard G. (Canadian Geriatrics Journal, 2022)
Background Suicide in older adults is a significant overlooked problem worldwide. This is especially true in Canada where a national suicide prevention strategy has not been established. Methods Using linked health-care administrative databases, this population-level study (2011 to 2015) described the incidence of older adult suicide (aged 65+), and identified clinical and socio-demographic factors associated with suicide deaths. Results The findings suggest that suicide remains a persistent cause of death in older adults, with an average annual suicide rate of about 100 per million people over the five-year study period. Factors positively associated with suicide vs. non-suicide death included being male, living in rural areas, having a mental illness, having a new dementia diagnosis, and having increased emergency department visits in the year prior to death; whereas, increased age, living in long-term care, having one or more chronic health condition, and increased interactions with primary health care were negatively associated with a suicide death. Conclusion Factors associated with suicide death among older adults highlighted in this study may provide better insights for the development and/or improvement of suicide prevention programs and policies.